(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article analyzes the artistic modeling of nature-human unity in folk epics and explores the poetic mechanisms through which the idea of ecological consciousness is shaped. The research methodology includes the ecocritical approach, the semantics of motifs and imagery, as well as comparative and discourse analysis. The findings demonstrate that ecological norms in epics are primarily encoded as ethical and social standards rather than mere environmental descriptions.